2012
DOI: 10.1016/j.energy.2012.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and experimental verification of a solar-powered liquid desiccant cooling system for greenhouse food production in hot climates

Abstract: Experiments and theoretical modelling have been carried out to predict the performance of a solar-powered liquid desiccant cooling system for greenhouses. We have tested two components of the system in the laboratory using MgCl 2 desiccant: (i) a regenerator which was tested under a solar simulator and (ii) a desiccator which was installed in a test duct. Theoretical models have been developed for both regenerator and desiccator and gave good agreement with the experiments. The verified computer model is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 48 publications
(71 reference statements)
0
31
0
Order By: Relevance
“…Temperature reduction of the air after evaporation process is limited due to the ambient high humidity, thus making the performance of such technology is not as satisfied as in the dry climate region. According to author's knowledge, the existing studies [21,22] that intended to improve such problem utilised auxiliary equipments like desiccators for air pretreatment. Besides, systems such as air conditioner or earth-to-air heat exchanger (EAHES) are usually applied in the humid climate to lower the interior air temperature but with the major disadvantage of the high initial cost as well as the subsequent operation and maintenance expenses [4].…”
Section: Introductionmentioning
confidence: 99%
“…Temperature reduction of the air after evaporation process is limited due to the ambient high humidity, thus making the performance of such technology is not as satisfied as in the dry climate region. According to author's knowledge, the existing studies [21,22] that intended to improve such problem utilised auxiliary equipments like desiccators for air pretreatment. Besides, systems such as air conditioner or earth-to-air heat exchanger (EAHES) are usually applied in the humid climate to lower the interior air temperature but with the major disadvantage of the high initial cost as well as the subsequent operation and maintenance expenses [4].…”
Section: Introductionmentioning
confidence: 99%
“…This is essential in hot and humid climatic areas where the efficiency of these direct systems is less [14]. Compared to conventional evaporative cooling, the desiccant system lowers average daily maximum temperatures in the hot season by 5.5-7.5 °C, sufficient to maintain viable growing conditions for vegetables crops throughout the year in greenhouses [15].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally obtained results indicated that the system was able to dehumidify 1.6 kg/s of process air at 30.1 • C dry-bulb temperature and 6.6 g/kg of humidity ratio which was equivalent to 17 • C wet-bulb temperature. A solar powered liquid desiccant air conditioning system for greenhouse food production in hot climates was proposed in [34]. As shown in Fig.…”
Section: Hybrid Solar Liquid Desiccant and Direct Evaporative Coolermentioning
confidence: 99%
“…The system is capable of dehumidifying 1.6 kg/sec of process air Lychnos and Davies [34] Solar powered liquid desiccant cooling system for greenhouse food production in hot climates…”
Section: Simulationmentioning
confidence: 99%